An ethnographic research on the educational marketing environment in rural Romania during the COVID pandemic 19 - Grigoroiu, Monica Claudia; Țurcanu, Cristina (INTED2023 Proceedings, 2023)
During the period marked by the COVID-19 pandemic, the educational marketing environment in the Romanian countryside has undergone a process of reconfiguration on all components of the marketing environment. In order to capture the implications of this reconfiguration process, an ethnographic research was conducted in 6 rural localities in Romania. The researchers spent 56 days in the communities under research, making working visits to schools, interacting with local people and children in different contexts, observing their behavior, concerns, educational habits, visiting the homes of community members, measuring the distances children have to travel to school, getting to know closely both children and their parents, talking to teachers and other professionals, working with rural pupils. All the components of the external marketing environment were analyzed: the demographic, economic, social-cultural, natural, technological and political-legal environment as this analysis is considered an important step in the strategic planning or strategic educational marketing process. Resources such as the geometry of place and power, socio-economic and cultural interactions, and financial resources strongly influence the educational aspirations of rural students and the trajectory of rural youth towards secondary and higher education. Ongoing investigation of the organizational environment, forecasting and identification of opportunities is part of the process of analysis and strategic planning in education that can enable organizational objectives to be achieved effectively and, where necessary, the desired correction to be made to the impact of the factors under analysis. This process includes the assessment of external influences on the organization of the education system, as determinants that could affect the quality of educational services offered in rural areas, together with the assessment of internal resources and their use. The research revealed that the external marketing environment cannot be controlled by the schools in the territory. Macro-environment factors are not subject to the influence of population groups, power structures, businesses located in the territory. In order to have a competitive school, it is necessary that it is always linked to the environment, the educational market and the beneficiaries. Strategic development implies a continuous and systematic flow of information regarding the school's internal and external environment, a dynamic relationship with the outside world.
Keywords: External educational marketing environment; COVID 19 pandemic; ethnographic research; rural education.